2005
DOI: 10.1177/014860710502900293
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis Gravidarum and Fetal Outcome

Abstract: Infants born of women who had HG are more likely to experience decreased gestational age and increased length of hospital stay. Efficacy of early and aggressive treatment of HG, including nutrition support, in minimizing these outcomes needs to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
3
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 22 publications
0
42
3
4
Order By: Relevance
“…Several studies have found similar and slightly higher reductions in birthweight. 6,8,[18][19][20] Other studies have not found a similar association.…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have found similar and slightly higher reductions in birthweight. 6,8,[18][19][20] Other studies have not found a similar association.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, other studies reported that just women with HG gaining less than 7 kg during pregnancy had a risk for PTB, LBW and increase in risk for a 5 minute Apgar score < 7 [7] .…”
Section: Introductionmentioning
confidence: 76%
“…HG has been reported to be associated with low birth weight (LBW), preterm birth (PTB), small-for gestational-age (SGA), perinatal mortality and prolonged stay in hospital for the new-born infant [7][8][9] . In contrast, other studies reported that just women with HG gaining less than 7 kg during pregnancy had a risk for PTB, LBW and increase in risk for a 5 minute Apgar score < 7 [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms range from mild to severe. Patients may present with weight loss exceeding 5% of their body weight, dehydration, ke- (9,10). Mild hyperthyroidism may be associated with HG, perhaps due to high serum concentrations of human chorionic gonadotropin, which may have more thyroid-stimulating activity in pregnant women (11).…”
Section: Clinical Featuresmentioning
confidence: 99%